Molecular mechanisms of glucose metabolism disorders in tumors of the female reproductive system - E. Yu. Kovaleva; R. R. Kantimirova; T. K. Gunina; E. V. Vlasenko; D. O. Salychin; D. S. Khulagova; A. Kochkin; V. A. Mamatkova; N. S. Zhakov; G. K. Bezmaternykh; E. Yu. Fomenko; A. A. Mullagalieva; et al. (Акушерство, гинекология и репродукция)
Glucose metabolism plays a pivotal role in fueling the energetic and biosynthetic demands in rapidly proliferating cells. In gynecologic malignancies (GMs), including ovarian cancer (OC), endometrial cancer (EC), and cervical cancer (CC), metabolic reprogramming occurs to support tumor growth, invasion, metastasis, and drug resistance. The current review provides a comprehensive analysis of the molecular mechanisms underlying glucose metabolism dysregulation in tumors of the female reproductive system, covering glycolysis, the tricarboxylic acid (TCA) cycle, and the pentose phosphate pathway (PPP). Special attention is paid to key enzymes such as hexokinase 2 (HK2), pyruvate kinase M2 (PKM2), lactate dehydrogenase A (LDHA), and 6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase (PFKFB3), which are central to the Warburg effect. The review also addresses transcriptional regulators such as hypoxia-inducible factor 1-alpha (HIF-1α) and metabolic sensors like pyruvate dehydrogenase kinase 1 (PDK1) and isocitrate dehydrogenase 1 (IDH1) that play important roles in the adaptation of tumor cells to hypoxic conditions and in disease progression. Expression profiles of glucose transporter 1 (GLUT1), glucose transporter 3 (GLUT3), sodium glucose cotransporter 1 (SGLT1) and PPP enzymes – glucose-6-phosphate dehydrogenase (G6PD), transketolase-like 1 (TKTL1), are discussed in the context of redox homeostasis maintenance and the development of chemoresistance. Understanding these metabolic alterations opens avenues for identifying potential therapeutic targets and prognostic biomarkers. Incorporating molecular profiling into clinical practice may facilitate the development of personalized therapeutic strategies and improve the prognosis of patients with gynecologic cancers.